Polycationic Glycopolymer Demonstrates Activity Against Persisters and Biofilms of Non-tuberculosis Mycobacteria Cystic Fibrosis Clinical Isolates in vitro - Narayanaswamy, Vidya P.; Townsend, Stacy M.; Loughran, Allister J.; Wiesmann, William; Baker, Shenda (Frontiers in Microbiology, 2022)
Nontuberculosis Mycobacterium (NTM) is a group of opportunistic pathogens associated with pulmonary infections that are difficult to diagnose and treat. Standard treatment typically consists of prolonged combination antibiotic therapy. Antibiotic resistance and the role of biofilms and tolerant pathogen communities such as NTM persister cells, is an important unmet challenge that leads to increased toxicity, frequent relapse, poor clinical management and an extended treatment period. Infection recurrence and relapse are not uncommon among individuals with cystic fibrosis (CF) or chronic obstructive pulmonary disease (COPD), where thick mucus supports bacterial biofilm production and impairs mucociliary clearance. The study evaluates a membrane-active cationic glycopolymer (poly (acetyl, arginyl) glucosamine (PAAG)) being developed to support the safe and effective treatment of NTM biofilm infections. The antibacterial activity demonstrated by PAAG shows activity against a wide range of pathogenic bacteria at concentrations non-toxic to human epithelial cells. Time-kill curves generated demonstrated PAAG’s rapid bactericidal potential at concentrations as low as 1X MIC against all NTM strains tested and compared to the standard of care. PAAG treatment prevents persister formation and eradicates antibiotic-induced persister cells in planktonic NTM cultures below the limit of detection. Further, PAAG showed the ability to penetrate and disperse NTM biofilms formed by both rapidly and slowly growing strains. PAAG treatment significantly reduced the biofilm biomass (P<0.0001) compared to the untreated NTM biofilms. Microscopical examination confirmed PAAG’s ability to disrupt and disperse mycobacterial biofilms. A single PAAG treatment resulted in up to a 25-fold reduction in live-labeled NTM and a 78% reduction in biofilm thickness. Similar to other polycationic molecules, PAAG’s bactericidal and antibiofilm activities employ rapid permeabilization of the outer membrane of the NTM strains, and subsequently, reduce the membrane potential even at concentrations as low as 50µg/mL (P<0.001). The outcomes of these in vitro analyses suggest the importance of the multivalent, polycationic glycopolymer, PAAG, as a potential therapeutic agent for opportunistic NTM infections.